A new method to improve raw water turbidity removal efficiency in sedimentation units with continuous discharges and flow recirculation - Ridwan; Bachtiar, Vera S.; Afrianita, Reri; Indriani, Rifka (Engineering and Applied Science Research, 2023)
The CDF method sedimentation tank is a new method that makes a continuous and controlled exhaust flow a new force acting on the particles to be removed, increasing the efficiency of turbidity removal. The exhaust flow, due to continuous and controlled leaks, causes the production capacity of the sedimentation tank to decrease. To maintain the production capacity of the sedimentation tank and to increase the efficiency of the turbidity removal, the effluent due to leakage is recirculated to the inlet of the flocculation tank. The research reactor consisted of a coagulation tank in the form of a waterfall, a flocculation tank in the form of a baffle channel, and a sedimentation tank using the CDF method. The research reactor was designed with a production capacity of 240 L/hour. To test the capability of increasing the production capacity of the sedimentation tank using the CDF method without increasing the number of sedimentation tank units which is referred to as the uprating process, an experiment was carried out in this study by increasing the production capacity to 360 L/hour or 1.5 times the capacity of the original reactor design. The variations in the recirculation of the effluent due to leaking at the bottom of the settling zone to the inlet of the flocculation bath were 0% (no recirculation), 25%, 50%, 75%, and 100% (all effluent recirculated). The results showed that the higher the CDF flow recirculation value, the higher the turbidity removal efficiency. The highest turbidity removal efficiency was achieved at a 100% CDF flow recirculation value which was 87.21% with a treated water turbidity of 3.267 NTU at a design discharge of 240 L/hour, while at a discharge of 360 L/hour, it was 82.50% with a treated water turbidity of 4.528 NTU.